2020
DOI: 10.21203/rs.3.rs-115748/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Training Needs Assessment of Health Care Professionals in Reproductive, Maternal and Newborn Health in a Low-Income Setting in Tanzania

Abstract: BackgroundHealthcare delivery globally and particularly in low-income setting is challenged by multiple, complex and dynamic problems. The reproductive, maternal and newborn health (RMNH) care is among the most affected areas resulting into high maternal and neonatal mortality and morbidity across the Sub Saharan region and Tanzania in particular. However, under-investment in adequate education and training of health care providers (HCPs) is reported worldwide and contributes to the critical shortages, and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These results may arise from differences in perception and performance, depending on the country’s level of healthcare and the presence and experience of qualified continuous professional training. In the current study, it was confirmed that a high proportion of participants (90.9%) had received clinical nursing training for high-risk premature infants, while Mbekenga et al [ 19 ] noted that there were issues such as a lack of quality education and training for healthcare providers, a lack of knowledge and skills among healthcare providers in neonatal nursing, and an unacceptably high neonatal mortality ratio.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These results may arise from differences in perception and performance, depending on the country’s level of healthcare and the presence and experience of qualified continuous professional training. In the current study, it was confirmed that a high proportion of participants (90.9%) had received clinical nursing training for high-risk premature infants, while Mbekenga et al [ 19 ] noted that there were issues such as a lack of quality education and training for healthcare providers, a lack of knowledge and skills among healthcare providers in neonatal nursing, and an unacceptably high neonatal mortality ratio.…”
Section: Discussionsupporting
confidence: 61%
“…The difference appears to have arisen in Lim et al [ 2 ] due to measuring performance converted into performance confidence. Another previous study [ 19 ] measured the importance of newborn care, targeting Tanzania’s registered nurses. The results demonstrated 92.6–98.7 out of 100 points, which—converted—is 4.63–4.94 points out of 5 points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation